Four-way regulation of mosquito yolk protein precursor genes by juvenile hormone-, ecdysone-, nutrient-, and insulin-like peptide signaling pathways - Hansen, Immo A.; Attardo, Geoffrey M.; Rodriguez, Stacy D.; Drake, Lisa L. (Frontiers in Physiology, 2014)
Anautogenous mosquito females require a meal of vertebrate blood in order to initiate the production of yolk protein precursors by the fat body. Yolk protein precursor gene expression is tightly repressed in a state-of-arrest before blood meal-related signals activate it and expression levels rise rapidly. The best understood example of yolk protein precursor gene regulation is the vitellogenin-A gene (vg) of the yellow fever mosquito Aedes aegypti. Vg-A is regulated by (1) juvenile hormone signaling, (2) the ecdysone-signaling cascade, (3) the nutrient sensitive target-of-rapamycin signaling pathway, and (4) the insulin-like peptide (ILP) signaling pathway. A plethora of new studies have refined our understanding of the regulation of yolk protein precursor genes since the last review on this topic in 2005 (Attardo, Hansen et al. 2005). This review summarizes the role of these four signaling pathways in the regulation of vg-A and focuses upon new findings regarding the interplay between them on an organismal level.